Evaluation of Plantain Peel Flour (Musa paradisiaca (L.) AAB cv. Curare enano) as a Sustainable Source of Dietary Fiber in the Elaboration of Cooked Pork and Beef Sausages - Castillo L., Ana F.; Soler S., Andrea G. (Zamorano: Escuela Agrícola Panamericana, 2022, 2022)
Currently, consumers are in search for food that provides good sensory experience, nutritional benefit, and aid health. The plantain industry has an enormous output of discarded peel that usually ends as animal feed or deposited in landfills without considering its nutritional characteristics. The main purpose of this research was to evaluate the elaboration of Plantain Peel Flour (PPF) as a source of dietary fiber in the production of cooked sausages. In the first phase, plantain peel flour was processed and its nutritional composition and the presence of Salmonella, Escherichia coli, molds, and yeast evaluated. The amount of dietary fiber present was determined to be 26.13 ± 1.42%. In the second phase, the cooked sausages were prepared in the Meat Plant Zamorano with three different formulations, in which potato starch (PS) and water was replace by PPF in this manner: T1:3.50% PPF 8% water added (WA), T2:6.32% PPF 5.28% WA, and T3:9.02% PPF 2.48% WA; being the plant’s standard cooked sausage, the control. Total coliforms and aerobic mesophilic bacteria were under the limit of regulations. A Complete Randomized Blocks Design was used for the sensory evaluations, it showed that the consumers preferred the plant’s cooked sausage over the other treatments. The physicochemical properties like pH, texture profile and color were different between the plant´s cooked sausage compared to the treatments with addition of PPF. T3 had 1.58 ± 0.14% of dietary fiber, considered a source of it. Further studies on meat replacement for PPF in the cooked sausages is proposed.